Rehabilitation of Red Mud Ponds at Indal, Belgaum (Karnataka) - Sharma, J. Y.; Lhouvum, Grace; Chauhan, Suresh; Lal, Banwari; Singh, T. P.; Paul, Varghese (Indian Forester, 2004)
Bauxite residue, also known as red mud, is a by-product of the Bayer Process. Bauxite is composed principally of the monohydrate and trihydrate forms of alumina in varying proportions. The research study was conducted to rehabilitate used red mud ponds of INDAL (Indian Aluminium Company Ltd.), Belgaum, Karnataka, India, by identifying suitable trees, grasses, and legume species as well as amenders, including bacteria and mycorrhizae, to improve the physico-chemical condition of red mud deposits and convert it to a substrate. Amenders such as gypsum, FYM (farmyard manure), fly ash/vegetative dust in different proportions, forming three basic combinations, A, B, and C, were developed. These three combinations were then treated with the bacteria and mycorrhizae both alone, and in combination, to form twelve treatments and one control. The research study showed that there is remarkable change in the physical and chemical properties of red muod after amendment, which provides the platform for plantation growth. The best combination found for treating red mud ponds was: Red mud + 20% FYM + 10% Gypsum + 15% Fly ash + Bacteria + Mycorrhizae for four tree species, Prosopis julijlora, Acacia nilotica, Pangamia pinnata and Melia azedarach, and three grass/legume species Brachiaria mutica, Chloris gayana, and Sesbania sesban.